Creating Mobile Telecom Markets in Africa - Sepulveda, Edgardo (International Finance Corporation, Washington, DC, 2018)
Mobile telecommunications has many benefits, from linking communities and citizens to mobile applications that bring financial services to the unbanked and help farmers improve crop yields. Yet at one time it looked as though Africa’s mobile sector might fare as poorly as its fixed line system did. Instead, an appropriate mix of regulation and competition, investment, and affordability allowed mobile phones and broadband access to flourish.